Removal capability of Carbon-Soil-Aquifer filtering system in water microbiological pollutants - W.B., Wan Nik; Rahman, Md. Mokhlesur; M.F, Ahmad; J., Ahmad; A.M., Yusof (http://www.intechopen.com/books/ecological-water-quality-water-treatment-and-reuse, 2012)

(untitled)
A newly fabricated filter unit as shown in Figure 4 has been found to be significantly improved for its removal capability of microbiological hazardous materials from the filtered water. It provides a safe drinking water in the point of view of microbiological, toxicity,softening hardness and pH value. All kinds of parameters for drinking water have fulfilled the requirements as provided by this water filter unit.